2022
DOI: 10.1111/cns.14027
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture ameliorates cerebrovascular impairment in Alzheimer's disease mice via melatonin signaling

Abstract: Aims: Cerebrovascular impairment contributes to the pathogenesis of Alzheimer's disease (AD). However, it still lacks effective intervention in clinical practice. Here, we investigated the efficacy of electroacupuncture (EA) in cerebrovascular repair in 3xTg-AD mice and its mechanism.Methods: 3xTg-AD mice were employed to evaluate the protective effect of EA at ST36 acupoint (EAST36). Behavioral tests were performed to assess neurological disorders. Laser speckle contrast imaging, immunostaining, and Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Furthermore, animal experiments have demonstrated that the ST36 acupoint could enhance the cognitive functions and slow down the progression of the central nervous system in animal models of AD. This was achieved through the activation of various signaling pathways such as TLR4/NF kB [ 44, 45 ], JNK [ 46 ], melatonin [ 47 ], RhoA/ROCK [ 48 ], and P38 [ 49 ], with a particular emphasis on restoring the balance of gut microbiota [ 46, 50, 51 ]. Simultaneously, our team has discovered, via several prior experimental investigations, that acupuncture could enhance the cognitive functions of SAMP8 mice by rectifying the dysbiosis of gut microbiota [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, animal experiments have demonstrated that the ST36 acupoint could enhance the cognitive functions and slow down the progression of the central nervous system in animal models of AD. This was achieved through the activation of various signaling pathways such as TLR4/NF kB [ 44, 45 ], JNK [ 46 ], melatonin [ 47 ], RhoA/ROCK [ 48 ], and P38 [ 49 ], with a particular emphasis on restoring the balance of gut microbiota [ 46, 50, 51 ]. Simultaneously, our team has discovered, via several prior experimental investigations, that acupuncture could enhance the cognitive functions of SAMP8 mice by rectifying the dysbiosis of gut microbiota [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This treatment approach also resulted in the decreased levels of APP, its C-terminal fragment (CTFs), and Aβ deposits, and inhibited glial cell activation in the prefrontal cortex and hippocampus of 5xFAD. Yu et al [ 176 ] and Yimin Jiang et al [ 178 ] assessed the improvement effect of acupuncture at different frequencies on AD mice, and they found that high-frequency EA exhibited promising results, effectively inhibiting the activity of GSK-3β in the presence of Aβ1-42. This inhibition led to a reduction in learning and memory impairments induced by Aβ1-42 and provided protection against damage to synaptic ultrastructure.…”
Section: Potential Mechanisms Of Traditional Chinese Medicine Natural...mentioning
confidence: 99%